Fjura facemask enterprise / Rafidah Abd Azis, Alya Zuri and Nurfatin Sorfina Azri - Abd Azis, Rafidah; Zuri, Alya; Azri, Nurfatin Sorfina (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
and sale of scented face masks. Our company is a start-up that specialises in producing fragrance face masks. We are considering both direct and indirect customer supply. In terms of indirect communication, we use media platforms such as WhatsApp, Instagram, Facebook, and Twitter. As a result, for direct services, we have retail shops in shopping malls where customers can walk in. Our company is located in various malls throughout the city of Selangor. Finally, after considering the business options and scanning the environment, we all agreed that purchasing this scented facemask would be the best option for us. We are confident that Fjura Facemask Enterprise will be well-received and well-known in our community. Furthermore, we sincerely desire that our customers who require rehabilitation or have a specific impairment improve their quality of life. To summarise, Fjura Facemask Enterprise is a vital and excellent initiative. As stated in our motto, we want to be among the top companies in the global face mask industry. We believe that our scented facemask can benefit people and make their lives better.